Târîhu’l-ümem ve’l-mülûk - 880-01 Taberî, Muhammed b. Cerîr, 839-923. (Kahire)
8 cilt (1. c. 639 sayfa ; 2. c. 664 sayfa ; 3. c. 576 sayfa ; 4. c. 608 sayfa ; 5. c. 632 sayfa ; 6. c. 574 sayfa ; 7. c. 616 sayfa ; 8. c. 167 sayfa)